A Comparative Diachronical Analysis of the Concept Tolerance in the English Language Speakers Consciousness - Nadezhda A. Nerovnaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2018)
The article is devoted to semantic and cognitive analysis of the tolerance concept in the English language native speakers' consciousness. A comparison of the data on tolerance obtained in publicist texts in 2007-2009 and in 2014-2016 revealed stable cognitive signs which proves the supposition that the concept under study is deeply rooted in the consciousness of native speakers of the English language. However, new cognitive signs and the signs which were not detected in 2007-2009, were noticed, thus pointing to reinterpretation of the tolerance concept. The field stratification of the concept was based on a traditional model with a nuclear and close, far, extreme periphery zones, into which the means that denote tolerance were included, whereas they are thought being different by the cognitive index of brightness. The studies highlighted one important trend – the increase index of negative appraisement which is the testimony to the fact that the attitude of the English language native speakers to the concept under investigation has negatively changed. The author comes to the conclusion that the concept is communicatively relevant and dynamic. The positive appraisement in the concept 'tolerance' structure prevails.